Synthesis and characterization of mixed oxides catalyst to produce fame / Siti Athirah Ramli and Dr Wan Zuraida Wan Kamis - Ramli, Siti Athirah; Wan Kamis, Wan Zuraida (2021)
Biodiesel known chemically as fatty acid methyl esters (FAME) is an alternative to fossil fuels. The process of transforming cooking palm oil into biodiesel is called transesterification reaction. Transesterification is the chemical reaction between a triglyceride and alcohol in the presence of the catalyst, producing a mixture of fatty acid esters and glycerol. Heterogenous catalyst is the preferred catalyst in this research due to the least problem to the overall reaction compared to homogenous catalyst and enzyme. The Mn-Al mixed oxides catalyst was synthesized via sol-gel method at different metal ratio and tested in the transesterification of FAME. The reactions were conducted in a batch reactor at temperature 55oC, methanol to oil molar ratio of 15:1 and catalyst loading of 2wt%. The thermal stability and presence of surface functional group were investigated using thermal gravimetric analysis (TGA) and Fourier-transform infrared spectroscopy (FTIR). The synthesis catalyst is also used for determination of FAME density by Micromeritic Pycnometer model AccuPyc II 1340. The result shows that catalyst with metal ratio 1:0 obtained FAME density of 864.9 kg/m3 which is the closest to the standard palm oil density. However, based on TGA analysis, metal ratio 1:2 has stable weight change at temperature 500 oC with the second closest FAME density of 861.4 kg/m3. Thus, the best catalyst based on this research is metal ratio 1:2 according to TGA analysis and FAME density. Thereby, this research highlights the recent effective investigation in prepare and characterize Mn-Al mixed oxides catalyst.